Calcium-activated chloride channel regulator 1 as a prognostic biomarker in pancreatic ductal adenocarcinoma - Hu, Dingyuan (BMC Cancer, 2018)
BACKGROUND: In a previous study utilizing mass spectrometry-based proteomics, we identified calcium-activated chloride channel regulator 1 (CLCA1) as a potential tumor suppressor in pancreatic cancer and the expression was inversely correlated with patient survival. The aim of the study was to further validate the prognostic significance of CLCA1 in pancreatic cancer. METHODS: CLCA1 expression was evaluated with tissue microarrays and immunohistochemistry in 140 patients with pancreatic ductal adenocarcinoma that underwent surgical resection at Skåne University Hospital, Sweden. Kaplan-Meier and Cox proportional hazards modeling were used to explore the association between CLCA1 and clinicopathological factors and survival. RESULTS: CLCA1 expression was denoted as positive in 90 tumors (64.3%), with positive staining being limited to the tumor cells. There were no significant association between CLCA1 expression and established clinicopathological parameters. Low CLCA1 expression correlated significantly with shorter disease-free survival (11.9 vs 17.5 months, P = 0.042). Multivariable Cox regression analysis confirmed the results (HR 0.61, 95% CI-0.40-0.92, P = 0.019). CONCLUSIONS: Low CLCA1 expression is an independent factor of poor disease-free survival in pancreatic cancer.